Comparison of the risk of fatal coronary heart disease in treated xanthomatous and non-xanthomatous heterozygous familial hypercholesterolaemia: a prospective registry study. - Neil, H; Huxley, R; Hawkins, M; Durrington, P; Betteridge, D; Humphries, SE (2003)
BACKGROUND: A clinical diagnosis of familial hypercholesterolaemia (FH) is often made in the absence of tendon xanthomata (TX), which are not usually present before the fourth decade of life. The prognosis of treated non-xanthomatous (TX-) FH is uncertain and the objective of this study was to compare mortality from coronary heart disease (CHD) in patients with treated TX+ (definite) and TX- (possible) heterozygous FH. METHODS: A diagnosis of definite or possible FH was based on raised cholesterol levels (>7.5 mmol/l) and a family history of premature CHD or hypercholesterolaemia. Patients were recruited from 21 outpatient lipid clinics in the UK from 1980 to 1998. The cohort of 1569 patients with TX+ FH were followed for 12754 person years and the cohort of 1302 patients with TX- FH for 10238 person years. The standardised mortality ratio (SMR) was calculated from the ratio of the number of deaths observed to the number expected in the general population of England and Wales (SMR=100 for reference population). FINDINGS AND DISCUSSION: CHD accounted for 64 (63%) of the 102 deaths in the TX+ cohort and 38 (57%) of the 67 deaths in the TX- cohort with the SMR for a fatal coronary event being, respectively, 294 (95% confidence interval 228, 380, P<0.00001) and 205 (95% CI 145, 282, P=0.0001). The similarly elevated CHD mortality risk suggests that, in adulthood, both groups of patients should be treated equally aggressively with HMG Co A reductase inhibitors (statins).